INVESTİGATİON OF THE EFFECT OF SOCİO-DEMOGRAPHİC FACTORS ON WOMEN'S EMPOWERMENT (Third Sector Social Economic Review, 2023)
This study was conducted to examine the effect of socio-demographic factors on women's empowerment. This research is a descriptive study and the study group of the research consists of 409 women with different socio-demographic characteristics living in Seyrantepe, Yuva and Ovacık district in Kırıkkale province, who voluntarily accepted to participate in the study. Research data were collected by a questionnaire form prepared by the researchers. The questionnaire form consists of 2 parts. In the first part, socio-demographic information about the women participating in the study is given. In the second part, the “Women's Empowerment Scale” compiled by the American Development Organization (USAID) as part of the Communication for Change Project (Change) and adapted into Turkish by Baydur and Uçan (2016) was used. In the evaluation of the data, descriptive statistics such as frequency, percentage, mean and standard deviation were used to determine the relationship between the variables and whether there was a significant difference between the two groups, the test of significance between two groups if the number of groups was two, and the One-Way Analysis of Variance (ANOVA) if the number of groups was more than two.According to the research results; Significant differences were determined between socio-demographic variables such as women's age, educational status, marital status, number of children, neighborhood of residence, monthly income level, age at first marriage and working status, and the Women's Empowerment Scale subscales.
Keywords: Family pressure; independence; economic security; women; women's empowerment; socio-demographic factors